Pitfalls in diagnosis of hepatitis B virus infection among adults Nigerians (2009)
"OBJECTIVE:Hepatitis B virus infection is common in Nigerians and its diagnosis is necessary for effective treatment and eradication. This study is aimed at highlighting the serological factors jeopardizing the diagnosis and treatment of the infection among Nigerians adults. PATIENTS AND METHODS:Three studies were carried out. The first study involved 56 Nigerian adults and it compared the assay of HBsAg by Haemagulation Method (HMA) with Enzyme linked immunoassay (ELISA). The second study was a comparison of Glaxo Welcome HB rapid test(GWHB) with ELISA in sero-assay of HBsAg and HBeAg among 25 Nigerian subjects while the third study was on the assay of the sera of HBsAg positive patients for HBeAg and anti-HBe in forty two Nigerian patients by ELISA. RESULTS:The sero - prevalence rates of HBsAg were 41.8% and 61.8% by HM and ELISA respectively with false HBsAg sero-positives and sero-negatives by HM of 5.4% and 25.5% respectively. Similarly, there was sero-detection of HBsAg in 84% and 80% by ELISA and GWHB respectively in 25 Nigerian adults. In addition, 19% and 64% of the 42 patients with HBsAg sero-positivity were also positive for HBeAg and anti-HBe respectively, while 31% of the patients were both HBeAg and anti-HBe sero-negative. CONCLUSION:Sero-diagnosis of HBsAg and other serological markers of infectivity in patients with HBV should be carried out by ELISA rather than HMA among adult Nigerians. Furthermore, high infectivity of the virus abounds among Nigerian with HBV infection."